A mistletoe kiss in Manhattan - Douglass, Traci (Harlequin medical romance, 2022)
Can a magical Christmas kiss in Manhattan melt the icy heart of the surgeon? Escape to New York for the holidays with the latest Harlequin Medical Romance by Traci Douglass.The surgeon grinch who stole......her heart!